LATE ARCHEAN (LOPIAN) GRANITE-GREENSTONE ROCK ASSOCIATION OF THE NORTHEASTERN BELOMORIAN MOBILE BELT, KOLA PENINSULA, RUSSIA - Chashchin V.V. (My University, 2004)
Geological mapping showed that the northeastern part of the Belomorian mobile belt consists of metamorphic rocks (amphibolites and schists) and plagiogneisses resting on a granite basement. The close spatial association of amphibolites and plagiogneisses and their petrogeochemical features suggest that they represent a single bimodal volcanic series typical of Late Archean granite-greenstone terranes. Metavolcanic rocks are composed of two types of structures: (1) monoclinal and troughlike in the southwestern part of the area and (2) linear strongly folded in the northeastern part. Based on the petrogeochemistry, the protolith of the amphibolites is interpreted as a primitive, weakly differentiated MORB-type tholeiitic basalt, while the protolith of the plagiogneisses appears to be andesite-rhyodacite volcanics. Granitoids of the basement are diorite-plagiogranites in petrography and tonalite-trondhjemites in normative composition. Petrogeochemically, they are similar to TTG granitoids of typical granite-greenstone terranes. They were presumably formed by the partial melting of mafic rocks of an older greenstone belt. The rocks composing the area were repeatedly metamorphosed, with the metamorphic peak at high-grade granulite facies, decreasing to high-temperature amphibolite facies.
Keywords: Archean; Precambrian::Archean; Докембрий::Архей